Olfactory Circuitry and Behavioral Decisions - Mori, Kensaku; Sakano, Hitoshi (Annual Review of Physiology, 2021)
In mammals, odor information detected by olfactory sensory neurons is converted to a topographic map of activated glomeruli in the olfactory bulb. Mitral cells and tufted cells transmit signals sequentially to the olfactory cortex for behavioral outputs. To elicit innate behavioral responses, odor signals are directly transmitted by distinct subsets of mitral cells from particular functional domains in the olfactory bulb to specific amygdala nuclei. As for the learned decisions, input signals are conveyed by tufted cells as well as by mitral cells to the olfactory cortex. Behavioral scene cells link the odor information to the valence cells in the amygdala to elicit memory-based behavioral responses. Olfactory decision and perception take place in relation to the respiratory cycle. How is the sensory quality imposed on the olfactory inputs for behavioral outputs? How are the two types of odor signals, innate and learned, processed during respiration? Here, we review recent progress on the study of neural circuits involved in decision making in the mouse olfactory system.
Keywords: pyramidal cells